2021
DOI: 10.28991/esj-2021-01258
|View full text |Cite
|
Sign up to set email alerts
|

Mathematical Modelling of the Relationship between Two Different Temperament Classifications: During the Covid-19 Pandemic

Abstract: In medicine, it is well known that healthy individuals have different physical and mental characteristics. Ancient Indian medicine, Ayurveda and the Persian-Arabic traditional Unani medicine has two distinct approaches for the classification of human subjects according to their temperaments. The individual temperament is an important foundation for personalized medicine, which can help in the prevention and treatment of many diseases including COVID-19. This paper attempts to explore the relationship of the ut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 29 publications
0
6
0
Order By: Relevance
“…One research showed that clients with diabetes mellitus have a higher frequency of hot and dry temperament than healthy controls (35) Another study demonstrated that temperament assessment using a questionnaire can provide important information for predicting the risk of hypertension in primary care (36). However, since the beginning of the COVID-19 epidemic, a few studies have been done on temperament, especially brain temperament, and its relationship with the COVID-19 severity (37). There is a bidirectional relation between mizaj and COVID-19 infection.…”
Section: Discussionmentioning
confidence: 99%
“…One research showed that clients with diabetes mellitus have a higher frequency of hot and dry temperament than healthy controls (35) Another study demonstrated that temperament assessment using a questionnaire can provide important information for predicting the risk of hypertension in primary care (36). However, since the beginning of the COVID-19 epidemic, a few studies have been done on temperament, especially brain temperament, and its relationship with the COVID-19 severity (37). There is a bidirectional relation between mizaj and COVID-19 infection.…”
Section: Discussionmentioning
confidence: 99%
“…The results obtained from analyzing condensed water captured from cold traps might help to identify critical factors that explain the daily fluctuations in patients infected by SARS-CoV-2, which usually includes information on the cumulative number of confirmed COVID-19 cases based on the combination of a nonlinear model and the number of completed swabs (Furlan & Mortarino, 2021). However, it should be clearly pointed out that the availability of respective cold traps might further increase the imbalance between rich and poor in preventing SARS-CoV-2 infections and the performance of the agri-food sector during the COVID-19 pandemic that is influenced by many more factors than other crisis in the world (Mizik, 2021;Rasheed et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…By using an analogy-based model, the findings of their study showed that temperature variation can impact the puff, halting its range by using extreme ambient cold or heat. By using a mathematical modeling approach, Rasheed et al (2021) explored the relationship between Indian medicine (Ayurveda) and Persian-Arabic medicine (Unani) to prevent and treat diseases including COVID-19. The authors elaborated that individual temperament is a significant factor for personalized medication and the results verified that it is mathematically possible to use Ayurveda and Unani treatment alternatively.…”
Section: Literature Reviewmentioning
confidence: 99%